(untitled) (Revista de Ensino em Artes, Moda e Design, 2022)
The present research seeks to understand the fashion narrative created by Jeremy Scott for the spring/summer + resort 2020 collection of the irreverent and fun brand MOSCHINO, and the implications and messages present in it through the ideology of horror, proposed by Barry Grant (2010), that permeates it. Furthermore, horror films and the celebration of halloween are brought to the discussion, along with their dynamics and pop culture status which involve the viewer in an immersive experience. These elements support the analysis of the show, from its setting to the pieces presented by designer Jeremy Scott. At the end, a reading of the analyzed fashion narrative is presented, which comprises MOSCHINO in the fashion world as a creative, playful brand, endowed with subversive potential that beckons to both sociocultural realities and pop culture.